2018
DOI: 10.1002/smll.201802934
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Au@Bi2Se3 Core–Shell Nanoparticle for Synergetic Therapy by SERS‐Traceable AntagomiR Delivery and Photothermal Treatment

Abstract: For the first time, topological insulator bismuth selenide nanoparticles (Bi Se NP) are core-shelled with gold (Au@Bi Se ) i) to represent considerably small-sized (11 nm) plasmonic nanoparticles, enabling accurate bioimaging in the near-infrared region; ii) to substantially improve Bi Se biocompatibility, iii) water dispersibility, and iv) surface functionalization capability through straightforward gold-thiol interaction. The Au@Bi Se is subsequently functionalized for v) effective targeting of SH-SY5Y cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 49 publications
0
29
1
Order By: Relevance
“…Based on these results, the proposed EC-LSPR dual detection biosensor composed of multi-functional DNA and AuNC exhibits simplicity, label-free detection, high sensitivity, and selectivity for the clinical assessment of AMI disease. Moreover, the proposed dual detection system can be tuned to sensitivity by introducing the plasmonic nanomaterials such as MoO 3 , MoS 2 and Bi 2 Se 3 , not only AuNC [32,33,34]. Additionally, the cross testing can reduce the detection error and increase the detection accuracy for portable AMI diagnosis system construction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the proposed EC-LSPR dual detection biosensor composed of multi-functional DNA and AuNC exhibits simplicity, label-free detection, high sensitivity, and selectivity for the clinical assessment of AMI disease. Moreover, the proposed dual detection system can be tuned to sensitivity by introducing the plasmonic nanomaterials such as MoO 3 , MoS 2 and Bi 2 Se 3 , not only AuNC [32,33,34]. Additionally, the cross testing can reduce the detection error and increase the detection accuracy for portable AMI diagnosis system construction.…”
Section: Discussionmentioning
confidence: 99%
“…In the XRD spectrum of Bi 2 Se 3 NPs ( Figure 1C), the peaks were well matched with standard value of Bi 2 Se 3 (JCPDS Card no 33-0214). [44,45] Additionally, the high magnitude TEM image of Bi 2 Se 3 ( Figure S5, Supporting Information) showed the lattice distance 0.208 nm, which represents [110] planes of Bi 2 Se 3 . All of the results verified the successful preparation of Bi 2 Se 3 .…”
Section: Preparation and Characterization Of Bi 2 Se 3 @Hemin-(g-h)-hmentioning
confidence: 99%
“…However, low water dispersibility, difficult functionalization and relatively low biocompatibility of Bi 2 Se 3 has restricted its biomedical applications. Although, Mohammadniaei et al reported that the encapsulation of Bi 2 Se 3 with gold can remarkably overcome those drawbacks [59,60], yet to explore more straight-forward methods.…”
Section: 2d Materials and Their Biomedical Applicationsmentioning
confidence: 99%